Bioactivities and green advanced extraction technologies of ginger oleoresin extracts: a review - Kamaruddin, Muhamad Syafiq Hakimi; Chong, Gun Hean; Mohd Daud, Nurizzati; Putra, Nicky Rahmana; Md Salleh, Liza; Suleiman, Norhidayah (Elsevier, 2023)
Zingiber officinale Roscoe is an excellent source of bioactive compounds, mainly gingerols and shogaols compounds, that associated with various bioactivities including antioxidant, anticancer, anti-inflammatory, antimicrobial, and antibiofilm. Zingiber officinale Roscoe found its application in the food, pharmaceutical, and cosmeceutical industries. The demand for a high quality of ginger oleoresin extracts based on the contents of gingerols and shogaols compounds for a health-benefit has dramatically increased. Various extraction techniques, including the conventional and advanced extraction techniques for gingerols and shogaols have been reported based on the literature data from 2012 to 2022. The present review examines the functional composition and bioactivities of Zingiber officinale Roscoe and the advanced green extraction technologies. Some variations in the quantity and quality of gingerols and shogaols compounds are because of the extraction method employed. This review provides a depth discussion of the various green advanced extraction technologies and the influences of process variables on the performance of the extraction process. Lower temperature with a short exposure time such as ultrasound-assisted and enzyme-assisted extraction, will lead to high quality of extracts with high content of 6-gingerol. High thermal processing, such as microwave-assisted and pressurized liquid extraction, will produce higher 6-shogaol. Meanwhile, supercritical fluid extraction promotes high quality and the safety of extracts by using non-toxic CO2. In addition, challenges and future prospects of the extraction of ginger oleoresin have been identified and discussed. The emerging green extraction methods and technologies show promising results with less energy input and higher quality extracts than conventional extraction methods.